PERTUNJUKAN INDANG TIGO SANDIANG DALAM ACARA BARALEK NAGARI DI KECAMATAN PATAMUAN KABUPATEN PADANG PARIAMAN: STUDI KOMPARATIF POLA RITEM - Alfredy Septoni; Wimbrayardi Wimbrayardi; Syahrel Syahrel (FBS Universitas Negeri Padang, 2014)
Abstract This research was designed for figuring out the similarities and the difference in Indang Tigo Sandiang show performed by three Indang Groups viewed from some rythem designs this was a content analysis research. The result of the research indicated that there were some similar rythem designs and motives used in the Tandikek Indang, Padang Sago, and Lubuak Aluang groups which were : Kata kunci: Indang Tigo Sandiang, comparative and contensanalysis